Hybrid Summarization for Brazilian Judicial Decisions - Araújo, Gabriele S.; Santana, Ewaldo E. C.; Lobato, Fábio M. F. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248671, 2026)
Research Context: Judicial decisions in Brazil have a complex textual structure, comprising reports, votes, and summaries, which hinders systematic analysis and affects information intelligibility. This also applies to many other countries in the Global South. This situation challenges not only legal professionals but also Information Systems (IS) that support the processing and organization of large volumes of documents. Scientific and/or Practical Problem: Many systems struggle with lengthy texts due to language model limitations and the need to preserve technical accuracy and cohesion. This restricts the development of reliable solutions for judicial activities and transparency. Proposed Solution and/or Analysis: This study proposes and evaluates a hybrid summarization pipeline for decisions from the Federal Supreme Court, integrating extractive and abstractive methods to handle long documents without information loss. Related IS Theory: The research is grounded in Task-Technology Fit (TTF), justifying the alignment between the pipeline and the legal summarization task to support information-processing objectives. Additionally, Design Science Research is employed as the methodology for artifact development and evaluation. Research Method: The pipeline was implemented and tested on the RulingBR corpus, which comprises Brazilian Supreme Court decisions. Five summarization methods were compared: TF-IDF (baseline), BumbaBERT, Gemini-2.5, and two hybrid variants, evaluated using standard metrics (ROUGE, BERTScore, and METEOR). Summary of Results: Hybrid approaches balanced technical accuracy and textual cohesion, while chunked processing expanded the applicability of specialized models to long documents. Results demonstrate practical impact through faster case review and improved jurisprudential research. Contributions and Impact on IS area: The study contributes to IS by proposing strategies that support information governance in organizational environments while considering processing limitations. Aligned with the Grand Challenge of IS in the Open World, it provides guidance for scalable, transparent, and interoperable decision-support systems, improving institutional transparency and supporting legal activities in complex digital ecosystems.